Psychological and behavioral examinations in cyber security - McAlaney, John, 1979-; Frumkin, Lara Anne, 1972-; Benson, Vladlena, 1976- (Information Science Reference, 2018)
"This book addresses the emerging importance of digital psychology and the opportunities offered by cyber researchers. It provides the resources necessary for academics, policy makers, technology developers and managers to improve cybersecurity and manage individual decision making more effectively"--